2018
DOI: 10.1108/md-10-2016-0745
|View full text |Cite
|
Sign up to set email alerts
|

Ethical consumption and consumers’ decision making: the role of moral intuition

Abstract: Purpose The purpose of this paper is to explore the understudied antecedents of moral reasoning and cognitive processes that ultimately shape the ethical consumption. The theory of planned behavior (TPB) and the socio-intuitionist model are integrated. Holistic, inferential, and affective dimensions of intuition are identified as critical antecedents of environmental concerns that then influence the ethical consumption. Design/methodology/approach Structural equation modeling is used to analyze intuitive jud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 49 publications
3
75
0
2
Order By: Relevance
“…In this context, the theory has been used to explore how consumer perceptions of a B2C e-commerce platform influence consumer attitudes toward an e-tailer and, in turn, the intention of e-loyalty. While the TPB traces its origins in the realm of psychology, over the last decade it has been widely adopted by marketing scholars (Rialti et al, 2017) and it has been useful in deconstructing the relationship between micro-mechanisms occurring in the inner self and consumers' behaviors (Zollo, Faldetta, Pellegrini and Ciappei, 2017;Zollo, Yoon, Rialti and Ciappei, 2018). It has also widely been adopted in digital marketing research about B2C e-commerce as it is capable to tackle the understanding about how consumers react to website's characteristics or e-tailer's stimuli.…”
Section: Bfjmentioning
confidence: 99%
“…In this context, the theory has been used to explore how consumer perceptions of a B2C e-commerce platform influence consumer attitudes toward an e-tailer and, in turn, the intention of e-loyalty. While the TPB traces its origins in the realm of psychology, over the last decade it has been widely adopted by marketing scholars (Rialti et al, 2017) and it has been useful in deconstructing the relationship between micro-mechanisms occurring in the inner self and consumers' behaviors (Zollo, Faldetta, Pellegrini and Ciappei, 2017;Zollo, Yoon, Rialti and Ciappei, 2018). It has also widely been adopted in digital marketing research about B2C e-commerce as it is capable to tackle the understanding about how consumers react to website's characteristics or e-tailer's stimuli.…”
Section: Bfjmentioning
confidence: 99%
“…According to De Mooij and Hofstede ( 2011 ), indeed, different cultures may cause differences in cognitive processes, information seeking and processing, and adoption of innovation. Similarly, they may cause dissimilarities in emotion arousal and inner motivations of consumers (Zollo et al, 2018 ). As a consequence, to better investigate and unfold these mechanisms, the present research will try to answer the following research question:…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consumers are increasingly concerned with ethical factors when forming their opinions about products and making purchase decisions (Brayet al, 2010). Several previous studies, Shaw Shiu (2002) and Zollo (2018) have revealed that consumers are actively considering factors related to supporting fair trade, labor rights, environment protection, welfare of animals, organically produced food products, boycotting products from unethical producers and others before making their purchasing and consumption decisions. Macovei (2015) stated that consumers' intention to behave in a certain matter is influenced by their actual behavior.…”
Section: Conceptual Frameworkmentioning
confidence: 99%